Genetic aspects of ischemic cerebrovascular diseases : (study of genetic markers on erythrocyte surfaces) - Božičević, Dubravko (Array, 1990)
This investigation focuses on the possible genetic differences between personssuffering from ischaemic cerebrovascular disease (iCVD) and a control population, based on five blood group systems: ABO, MN, Ss, Rh and P. The study group includes 50 patients whose diagnosis was confirmed with computed axial cerebral tomography. The control group includes 1883 persons randomly selected from 5 phenotypically healthy populations in Croatia. The MN and ABO genetic loci have the highest discriminating value. This study concludes that these antigens can help to differentiate iCVD patients from a phenotypically healthy population. Thus, this method can be used to identify persons at high risk for cerebrovascular disease